2002
DOI: 10.1124/jpet.302.3.1013
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin (CI-1008) Inhibits the Trinitrobenzene Sulfonic Acid-Induced Chronic Colonic Allodynia in the Rat

Abstract: In human, digestive disorders are often associated with visceral pain. In these pathologies, visceral pain threshold is decreased indicating a visceral hypersensitivity. Pregabalin [CI-1008; S-(ϩ)-3-isobutylgaba] presents antihyperalgesic actions in inflammatory somatic pain models. This study was designed to evaluate 1) the effect of injection of TNBS into the colon on visceral pain threshold, and 2) the antihyperalgesic effect of pregabalin on TNBS-induced chronic colonic allodynia. A significant decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 36 publications
8
68
1
1
Order By: Relevance
“…The presence of somatic hypersensitivity is a new finding as previous studies using TNBS colitis in rats have only evaluated colonic hypersensitivity [20][21][22][23][24]. There have been several previous studies that have used other visceral cavities (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of somatic hypersensitivity is a new finding as previous studies using TNBS colitis in rats have only evaluated colonic hypersensitivity [20][21][22][23][24]. There have been several previous studies that have used other visceral cavities (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To measure the pain threshold in response to colonic distension, we used behavioral signs of pain as an endpoint in the TNBS-induced visceral hypersensitivity model. This endpoint has been previously used and defined as a pain response in other studies because morphine showed potent efficacy on TNBS-induced visceral hypersensitivity (11). Using this endpoint, we demonstrated that PF-03550096 significantly inhibited TNBS-induced visceral hypersensitivity; this effect was reversed by the CB 2 -selective antagonist SR144528.…”
Section: Discussionmentioning
confidence: 74%
“…Sham animals underwent the same surgery but were not administered TNBS. Seven days after surgery, colonic pain threshold was measured as previously reported (11,12). Animals were fasted for 16 -18 h and then placed individually into polypropylene cages.…”
Section: Visceral Hypersensitivity Modelmentioning
confidence: 99%
“…The maximum doses of gabapentin and morphine selected were 200 and 5 mgÁkg -1 , respectively, based on similar studies, 4,9,14,16 while the maximum dose for pregabalin, which was novel in this model, was presumed to be 200 mgÁkg -1 . 8 The dose used for the dose-response data was the maximum dose and simple divisions ( , …) of that dose. Dilutions were made in normal saline so that a volume of 1/100 of mouse body weight would be injected.…”
Section: Acetic Acid-induced Writhingmentioning
confidence: 99%
“…7 Previous reports have shown that pregabalin inhibits trinitrobenzene sulfonic acid-induced allodynia in rats, and gabapentin inhibits acetic acid-induced irritation in rats. 8,9 Both pregabalin and gabapentin are recognized to reduce pain behaviour in colorectal distension and stress-induced visceral pain in rats. 10,11 Visceral pain still constitutes a large portion of clinically treated pain.…”
mentioning
confidence: 99%